An unusual cause of caecal perforation in a child - Simpkin V; Lakhoo K (Wolters Kluwer Medknow Publications, 2009)
Faecolith impaction leading to caecal perforation is a rare cause of acute abdominal pain in children. We present a case of an 11-year-old boy who was admitted to our department with a perforated caecum caused by faecolith impaction. Histology demonstrated a normal appendix with ganglion cells present. No mechanism of action could be detected for the faecolith impaction. This is a previously unreported cause of caecal perforation in children.